Role of the CS1 adhesion motif of fibronectin in T cell adhesion to synovial membrane and peripheral lymph node endothelium. Issue 9 (September 1993) - van Dinther-Janssen, A C; Pals, S T; Scheper, R J; Meijer, C J
Abstract : OBJECTIVES--It has previously been shown that the very late antigen-4/vascular cell adhesion molecule-1 (VLA-4/VCAM-1) pathway functions as a receptor/ligand interaction system mediating the recruitment of activated lymphocytes to inflamed synovium of patients with rheumatoid arthritis. This study was performed to determine whether VLA-4 also affects lymphocyte adhesion to inflamed synovium through interaction with the alternatively spliced CS1 domain of fibronectin. METHODS--The effect of the synthetic peptide CS1 on lymphocyte binding to human synovial and peripheral lymph node high endothelial venules (HEVs) was measured in an in vitro frozen section assay. RESULTS--In the presence of the CS1 peptide or antibody to fibronectin, significant inhibition of binding was observed (54 and 51% respectively). Blocking with antibody to VCAM-1 yielded inhibition of binding to 46% of the control value. Maximum inhibition of binding was obtained with a combination of antibody to VCAM-1 and CS1 (65%) and with antibody to VLA-4 alpha (68%). Blocking the classical fibronectin receptor with antibody to VLA-5 alpha gave a slightly lower inhibition at 42%. In normal peripheral lymph nodes, the synthetic peptide CS1 and antibodies to fibronectin and VLA-5 also partially inhibited T cell binding to HEVs (45, 47, and 52% respectively). CONCLUSION--These results show that fibronectin mediates lymphocyte-HEV interactions not only through its classical VLA-5 receptor, but also through its CS1 adhesion motif in inflamed synovium and peripheral lymph nodes.